Musical Composition Scale Chart - Singh, Akash; Singh, Ashutosh; Rana, Vikram; Shubham, Kumar (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2023)
Abstract Nowadays, everyone enjoys music greatly, and some people even more so. They produce fresh songs and put it out under their own name. However, they encounter some difficulties when they try to compose music since they must first choose the right note and then match the right scale to it. Here, we created an app that would assist them in determining the appropriate scale based on the notes they have provided as a fix. This is a novel idea because we searched and couldn't find anything similar that had been created to assist, so we decided that this would be the best course of action as everyone has a desire to be a musician and can explore that desire through this.Basically, tkinter is used to design the user interface for better looking of any website or app and one thing that makes it easy to use and code. We built it with the assistance of Python-Tkinter since python is simple to grasp and write and tkinter is good and easy for designing anything. Thus, we decide on Python-Tkinter. Anyone who wants to learn or create, such as a skilled musician, a novice, or a student, can benefit from this.